2021
DOI: 10.4062/biomolther.2020.226
|View full text |Cite
|
Sign up to set email alerts
|

Differential Signaling and Virus Production in Calu-3 Cells and Vero Cells upon SARS-CoV-2 Infection

Abstract: Severe acute respiratory syndrome CoV-2 (SARS-CoV-2) is responsible for the current coronavirus disease 2019 (COVID-19) pandemic. Signaling pathways that are essential for virus production have potential as therapeutic targets against COVID-19. In this study, we investigated cellular responses in two cell lines, Vero and Calu-3, upon SARS-CoV-2 infection and evaluated the effects of pathway-specific inhibitors on virus production. SARS-CoV-2 infection induced dephosphorylation of STAT1 and STAT3, high virus pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 38 publications
7
37
0
Order By: Relevance
“…We monitored the arginylation levels of one major cytoskeleton protein, ACTB, and we observed its increase in the first 2h after infection in Calu-3 cells, with a decrease at 48h, when apoptosis-related proteins were activated 17 . The ACTB arginylation pattern was different in infected Vero cells, as was already observed for phosphorylation 89 . Such observed difference stressed the importance to use multiple cell models to assess the cellular consequences of post-translational modifications in SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 62%
“…We monitored the arginylation levels of one major cytoskeleton protein, ACTB, and we observed its increase in the first 2h after infection in Calu-3 cells, with a decrease at 48h, when apoptosis-related proteins were activated 17 . The ACTB arginylation pattern was different in infected Vero cells, as was already observed for phosphorylation 89 . Such observed difference stressed the importance to use multiple cell models to assess the cellular consequences of post-translational modifications in SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 62%
“…We have previously reported that SARS-CoV-2 infection induces STAT3 phosphorylation in Calu-3 cells (21), and others have demonstrated that STAT3 influences MUC1 expression in lung cancer cells (22). Therefore, we investigated the effect of STAT3 inhibitors, including AG490, JAK inhibitor I, and S3I-201, on MUC1-C expression.…”
Section: Muc1-c Expression Is Dependent On Stat3 Activation In Calu-3 Cells After Sars-cov-2 Infectionmentioning
confidence: 94%
“…SARS-CoV-2 amplification and quantification was performed as described previously with minor modifications (21,31,32), and detailed information is provided in the Supplementary Material. SARS-CoV-2 amplification and cell culture procedures were performed in biosafety level 3 (BSL-3) conditions.…”
Section: Virus Amplification and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Calu-3 cells express ACE2 on the apical membrane domain and are infected by SARS-CoV-2 via this route. The higher number of Vero E6 infected cells is also associated with the differences in viral entry pathway and the expression of pro-apoptotic proteins, which increased drastically in these cells but not in Calu-3 cells (Banerjee et al, 2020;Murgolo et al, 2021;Park et al, 2021;Saccon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%